Smart city and e- government components - Bani Younes, Mohammad; Zeyad Aljunaedi, Bajes (International Journal of Engineering and Technology, 2018)
This theoretical paper will discuss the strategies and application of these plans for making the cities glamorous. A customary of the mutual multifaceted components causing the smart city concept and the essential features for an effective smart city project is acknowledged by discovering current working explanation of trendy city and a variety of numerous theoretical links analogous to smart city.Motivation: There is a need for considering smart cities for discussing the revolution in city governments and for the self-motivated of various investors.Problem statement: need to explore the ways of changing smart technologies and how the human factors are influenced by the smart cities with the advanced technologies.Method: review the studies of smart city frameworks.Contribution: This paper proposed planned ideologies line up to three main scopes such as people, skills, and the institutions of these trendy cities. It will also specify to integrate the facilities related to technology and organizations, and social education for the enhancement of the structure of human, governance that will make improvements in the engagements of citizen.Conclusion of research: have discovered the large number of theoretical scopes of smart in this paper that will be helpful for future studies as conceptual framework.Â Â Â